Case Report: Epididymal NK/T-cell lymphoma and adrenal diffuse large B-cell lymphoma are misdiagnosed as tuberculosis: two case reports and literature review - Ye, Dan; Liu, Xuhui; Yang, Yuexiang; Yang, Yang; Fei, Zhentao; Liu, Huarui; Zhan, Qilin; Xia, Lu (Frontiers in Oncology, 2025)
Extranodal NK/T-cell lymphoma(ENKTCL) and diffuse large B-cell lymphoma(DLBCL) are specific subtypes of non-Hodgkin lymphoma(NHL), which lack specific features and are difficult to diagnose. The clinical features of lymphoma and tuberculosis are similar, which are easy to be misdiagnosed and lead to delayed treatment. This report describes two cases, one that of a 34-year-old man who was diagnosed with epididymal tuberculosis because of fever, progressive epididymal enlargement, positive T-cell Spot Test(T-SPOT), and epididymal magnetic resonance imaging(MRI) suggesting possible epididymal tuberculosis. He was treated with anti-tuberculosis therapy for 1 month, but the patient’s epididymis continued to grow. Needle biopsy pathology and immunochemical examination showed an epididymal NK/T cell lymphoma, which gradually shrank after chemotherapy. Meanwhile, a 77-year-old female patient was reported who was diagnosed with adrenal tuberculosis because of fever, night sweats, abdominal pain, positive QuantiFERON-TB Gold(QFT) test, and adrenal tuberculosis detected by positron emission tomography/computed tomography(PET/CT). She received anti-tuberculosis treatment for 2 weeks, but her symptoms were not improved. Biopsy pathology and immunochemical examination showed adrenal diffuse large B-cell lymphoma, which deteriorated rapidly after chemotherapy and she finally died. In this report, epididymal NK/T cell lymphoma and adrenal diffuse large B-cell lymphoma are rare, and the disease develops rapidly. The diagnosis depends on pathological morphology and immunohistochemistry. Early detection, diagnosis, and treatment are crucial for the prognosis of patients.